Analisis Rasio Aktivitas untuk Menilai Kinerja Keuangan pada PT. Vale Indonesia Tbk Periode 2022-2024 - Sore, Yurlin; Audri, Ananda; Melani, Gita; Munawir, Munawir; Yunus, Muhammad Haekal (Pusat Riset dan Inovasi Nasional, 2025)
This study aimed to examine the financial performance of PT Vale Indonesia Tbk during the 2022–2024 period using an activity ratio analysis approach. The research method used was quantitative, with data sourced from the annual financial reports officially published on the Indonesia Stock Exchange. The analysis process utilized four main indicators: Receivable Turnover (RTO), Working Capital Turnover (WCTO), Fixed Assets Turnover (FATO), and Total Assets Turnover (TATO). These four ratios were chosen because they provide an overview of the company's effectiveness in utilizing assets and working capital to support sales activities. The results of the study indicate that PT Vale Indonesia Tbk's financial performance remains relatively poor, as all activity ratios tend to be below applicable industry standards. Although there was a slight increase in the RTO ratio, overall, this increase was not significant enough to indicate performance improvement. Management of receivables, working capital, fixed assets, and total assets remains suboptimal, resulting in a very limited contribution to sales growth. These findings confirm that low activity ratios can be used as an indicator of a company's weak effectiveness in utilizing its resources. Therefore, more targeted managerial improvement steps are needed, such as strengthening receivables management policies, increasing the efficiency of asset use, and implementing working capital optimization strategies so that the company's financial performance can improve in the future.